(untitled) (AYUSHDHARA, 2022)
Infertility is a global public health issue with an estimated prevalence of infertility ranging from 3.5% to 16.7% in more developed nations and from 6.9% to 9.3% in less developed nations. Female fertility is achieved by coordinated and synchronized functions of Garbha Sambhava Samagri. This synchronization may get disrupted due to various factors or dysfunction of reproductive tract like Artavadushti, Asrugdara, neuroendocrine system like Apanavayu vikruti, and immune system or by any severe systemic disease. According to Ayurveda, essential factors to achieve fertility are described as Garbha Sambhava samagri, incorporating disease free Kshetra, Rutu, Ambu and Bija and normal psychology (mind) and regulated Vata function at the general as well as specific level are also essential. Many formulations are described in Ayurvedic texts for the management of Infertility. But in the present paper an attempt is being made to present clinical observations of one folklore regimen comprising Jatiphala churna (given three days during Rutukala) and Ashvattha Jata (given during secretary phase). Clinical observations of four infertility cases are presented in the present paper; among the four, three are primary infertility cases and one secondary infertility case. Among the four, two cases got conceived and in two cases regularization of menses, ovulation induction observed. On overall observation, this regimen is giving encouraging results.